Peran Mahasiswa KKN UINSU dalam Edukasi Literasi Keuangan Sejak Dini pada Siswa SD di Desa Nagaraja - Aula Salsabila; Wahyu Ilahi Surya; Siti Aisyah (Pusdikra Publishing, 2026)
The low level of financial literacy among elementary school-aged children remains a problem, particularly in rural areas. Children generally are unable to manage their pocket money effectively and do not understand the difference between needs and wants. This situation highlights the need for early financial literacy education through community service activities. This community service activity aims to increase the understanding and awareness of elementary school students in Nagaraja Village regarding simple money management, including understanding the function of money, the difference between needs and wants, and instilling savings habits from an early age. The program was conducted by KKN students from the State Islamic University of North Sumatra (UINSU) in Nagaraja Village, Sipispis District, Serdang Bedagai Regency, North Sumatra, using a participatory approach through simple material delivery, educational games, money management simulations, and savings practices using piggy banks. The target group for this activity was fifth-grade elementary school students. He results of the activity showed that students experienced an increased understanding of the basic concepts of financial literacy. Students were able to re-explain the meaning of saving, provide examples of needs and wants, and demonstrate interest in setting aside their pocket money. The students' enthusiasm during the activity demonstrated that interactive and contextual learning methods are effective in financial literacy education for elementary school-aged children.